Desarrollo de un ecualizador paramétrico de fase lineal y comparación de su aplicación en procesos de calibración de estudios frente a ecualizadores con respuesta en fase no lineal - Agudelo Elejalde, Santiago (Ingenierias, 2017)
Analog equalizers and most of the digital equalizers used in audio systems lead to a phase change in the signal, because of that, both, destructive interference and frequency response changes appear; for this reason, a mastering engineers, who needs an accurate result, use linear phase equalizers in order to obtain the most precise signal processing. This investigation was made in order to compare the frequency response obtained as a result of the calibration of a stereo sound system placed in the Studio C of the San Buenaventura University with a linear and non-linear phase equalizers. A Matlab algorithm was developed and both, a linear phase EQ and non-linear phase EQ were obtained. After that, a frequency response measurement was performed using two different software applications (Room EQ Wizard and Smaart Live 7) in order to analyze the differences between the equalizers created in Matlab and the dbx 2231 analog equalizer.